Report on the Beveridge proposals
1943-01-19 1943 1940s 20 pages 15. Societies have proved their capacity for beneficial and economical administration, and while supersession would no doubt bring about complete uniformity for health insurance, there is no evidence that this change is desired by the insured persons themselves. At the same time, this section recognises the fact that anomalies are produced by the varied experience of the separately valued societies, in that one section of the insured may have the advantage of certain essential services, like dental or opthalmic benefits, while another section, though paying identical contributions, are denied such benefits. It therefore feels that essential treatment services ought to be available to all the insured; and to assist in bringing about such a reform, at least 50% of the disposable surpluses of Approved Societies should be pooled for distribution amongst all the Societies. Moreover, the Committee cannot regard it as other than illogical to abolish one set of Approved Societies and to retain the Friendly Societies and Trade Unions as agents for the distribution of State benefits. 4. OLD AGE PENSIONS. Should old age pensions be conditional on retirement? The Committee agreed with the principle of universal contributions for pensions, providing the problems of enforcement (referred to by Sir William Beveridge himself at p.54 of his Report) can be solved; and a majority were in favour of the principle of pensions being conditional on retirement. This would mean (following the recommendation under (No. 2) that there would be an income limit for Health Insurance but no income limit for Pensions. 5. WORKMEN'S COMPENSATION. Should Workmen's Compensation be included in a contributory Insurance Scheme and be administered by a State Office rather than as now by the Insurance Companies? The Committee also found itself divided in its views regarding the future of Workmen's Compensation. 200/B/3/2/C216/5/93